2022
DOI: 10.1186/s12902-022-01042-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum liver enzymes and diabetes from the Rafsanjan cohort study

Abstract: Background We evaluated the relation between ALT, AST, GGT and ALP with diabetes in the Rafsanjan Cohort Study. Materials and methods The present study is a cross-sectional research including 9991 adults participated via sampling. We used data obtained from the Rafsanjan Cohort Study (RCS), as a part of the prospective epidemiological research studies in IrAN (PERSIAN). Elevated serum levels of ALT, AST, GGT and ALP were defined according to the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 53 publications
(78 reference statements)
2
20
1
Order By: Relevance
“…These findings were comparable to the previous studies. [22,23] As much as 71.2% of the general population and 70.0% of the T2DM population in previous study have abnormal LFTs. [24].…”
Section: Discussionmentioning
confidence: 70%
“…These findings were comparable to the previous studies. [22,23] As much as 71.2% of the general population and 70.0% of the T2DM population in previous study have abnormal LFTs. [24].…”
Section: Discussionmentioning
confidence: 70%
“…With increasing age, the prevalence of abnormal ALT declines significantly among the Tehranian population, an issue that was addressed in previous studies 9,42,46 . As reported by Mahady et.al, 42 each decade increase in age decreases the odds of elevated ALT by 29% among Australians, while this was reported to be 18% in the Dutch population 45 .…”
Section: Discussionmentioning
confidence: 88%
“…In the previous nested case–control study in TLGS, Tohidi et.al 49 showed that among liver enzymes, only ALT was significantly associated with T2DM even after adjustment with classic risk factors[3.18 (1.02–9.86)]. In another study, a dose–response increase was reported for ALT and T2DM 9 . However, in our study, both genders showed a significant association between high FPG and abnormal ALT, but most of the studies reported this association only among women 44,50,51 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The quartiles for GGT levels in men were: ≤18 U/L, 19–23 U/L, 24–31 U/L, and 32–54 U/L, while for women the quartiles were: ≤14 U/L, 15–18 U/L, 19–23 U/L, and 24–37 U/L. The quartiles for ALP levels in both genders included: ≤177 U/L, 178–209 U/L, 210–244 U/L, and 245–306 U/L 22 …”
Section: Methodsmentioning
confidence: 96%